Augmented reality application for chemical engineering unit operations - Gunawan, Poernomo (Springer, Singapore, 2022)
Understanding unit operations is an essential part in chemical engineering course. An important example is the continuous distillation column, which operation is often seen as a black box, where the incoming feed will undergo separation process inside the column to produce desired products. Despite having learned the concepts on how they work, students may find it difficult to comprehend and visualize what is going on inside a distillation column and how to connect various theories involved in the design and calculations. By developing a virtual visualization tool, such as augmented reality (AR), students can better visualize the process, such as fluid flow profiles and different components that make up a distillation column. Although the idea of incorporating AR for higher education learning is not entirely new, this is the first initiative to implement virtual technology for chemical engineering curriculum in Singapore, which serves as a novel pedagogical approach to complement the conventional pen-and-paper teaching method. Besides enhancing the students’ learning experience, it is believed that the AR application would provide a way to improve the students’ motivation and interest to learn the subject as well as a complementary tool for laboratory demonstration, as it is practically safe and time-saving.